Hubungan di antara komitmen organisasi dengan niat berhenti kerja :kajian di CMS cement dan Bank Muamalat - Ahmad Dis, Bin Bukaria. (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study aimed to determine the influence of organizational commitment factor and demographic factor on turnover intention .Organizational commitment are includes affective commitmen t, continuance commitment and normative commitment, while demographic factors are include gender, age and years of service. This study was conducted in CMS Cement and Bank Muamalat. This sample of this study consist of 80 employees, there are 30 employees of Bank Muamalat and 50 employees a of CMS Cement. This study was used quantitative methods through distribute questionnaires to the respondents. There were 120 questionnaires distributed but only 80 questionnaires were returned. Data was analyzed using the Statistical Package for Social Science (SPSS) version 18.0. The result from this research show all the organization commitments there were affective commitment, continuance commitment and normative commitment has a significant correlatio n with the turn over intention while demographic factors there are gender, age, and length of service does not have significant correlation with the turnover intention. Continuance commitment is the most dominant factor affecting the turnover intention.